Mapping the Integration of Digital Technology in Mathematics Learning for Children with Disabilities in Inclusive Early Childhood Education: A Bibliometric Study - Sungwa, Reuben; Pembe, Alphoncina (International Journal on Studies in Education, 2025)
This bibliometric study analyzes research trends on the integration of digital technology in mathematics learning for children with disabilities within inclusive early childhood education settings. Using bibliometric methods, the study examines publication output, authorship patterns, productive institutions, and key thematic areas over the past two decades. The findings reveal a gradual increase in research activity, with a notable surge during the COVID-19 pandemic, highlighting the growing importance of digital tools in inclusive education. However, the overall volume of publications remains low, with contributions concentrated in high-income countries such as the United States and Russia. Leading authors, including Augestad, Liv Berit and Drigas, Athanasios, have made significant contributions, though the field lacks widespread scholarly engagement. Notably, journals such as Integration of Education and Education Sciences have published the most influential studies, while institutions like the Norwegian University of Science and Technology and STATPED have been among the most productive. The study also identifies gaps in curriculum integration, pedagogical strategies, and accessibility in low-resource settings. By addressing these gaps, the study aims to inform future innovations in digital technology and foster equitable access to quality mathematics education for children with disabilities. The findings emphasize the urgency of integrating research, policy, and practice to create inclusive learning environments that empower all learners.